2020
DOI: 10.1039/d0ra07808e
|View full text |Cite
|
Sign up to set email alerts
|

Possible dissolution mechanism of alkali lignin in lactic acid-choline chloride under mild conditions

Abstract: In this study, several representative deep eutectic solvents (DESs) were designed to evaluate the solubility for alkali lignin (AL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
1
Order By: Relevance
“…It is based on the principle that the reaction of isophosphotungstate—molybdate with phenolic hydroxyl groups—appears blue and is strongly proportional to the number of total phenolic hydroxyl groups, and is suitable for spectrophotometric determination. This method allows a rapid and simple determination of phenolic hydroxyl groups in lignin [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is based on the principle that the reaction of isophosphotungstate—molybdate with phenolic hydroxyl groups—appears blue and is strongly proportional to the number of total phenolic hydroxyl groups, and is suitable for spectrophotometric determination. This method allows a rapid and simple determination of phenolic hydroxyl groups in lignin [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various DES-like mixtures [30] were tested in this work to dissolve alkaline lignin, and a microscope, FT-IR, and NMR were used for subsequent analysis of the lignin composition.…”
Section: The Effect Of Des-like Mixtures On Model Samples and Machine...mentioning
confidence: 99%
“…When using DES-like mixtures based on choline chloride/lactic acid for the extraction of lignin from softwood, a higher lignin extraction (56.7-77.7%) was achieved than when extracting lignin from brewer's draff (34.5-39.3%), which may be due to the difference in % lignin in the input biomass, the complexity of the structure of lignin, or the different presence of lignin subunits (G, H, and S). Furthermore, the results revealed that acidic DES-like mixtures with a carboxylic acid, such as HBDs (lactic acid; pK a = 3.08), achieved a higher extraction efficiency than another type of HBD (glycerol; pK a = 14.15) [30]. FT-IR images revealed that DES-like mixtures based on choline chloride/lactic acid were able to extract lignin from biomass but did not cause adverse reactions by forming esters by binding through phenolic hydroxyl groups of lignin subunits by grafting.…”
Section: Fractionation Of Lignocellulosic Materials Using Des-like Mi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hal tersebut dapat terjadi karena lignin merupakan komponen yang sangat sulit didekomposisi, baik dengan perlakuan fisik seperti pemanasan, atau dengan perlakuan lain seperti fermentasi. Liu et al (2020) menyatakan bahwa lignin merupakan salah satu dari tiga komponen utama lignoselulosa yang terkondensasi stabil, sehingga sulit untuk dihancurkan dengan perlakuan suhu yang tinggi atau gelombang mikro. Kadar lignin pada bekatul gandum pada lama pemanasan 15 menit sebesar 0,8-0,11%, dan pada lama pemanasan 30 menit sebesar 0,5-0,7%.…”
Section: Profil Serat Bekatul Gandumunclassified